Automotive fundamentals fundamentals of engine performance (New Jersey : A Shopware Production, 2004)
This CD-ROM introduces the basic concept of engine performance. By covering the purpose-function and operation of the primary automotive systems involve in engine performance. This program also explain how the performance of an automobile can be optimized while the emissions produced and minimized.
System requirements: 200 MHz processor, 32 MB RAM (64MB preferred), 4 x cd-rom drive, 800 x 600 display with 256 colors, soundcard and speakers or headphones, keyboard, mouse, QUICKTIME 4 or higher, Adobe Acrobat Reader.
Keywords: Automobiles; Motor vehicles; Mechanical engineering